Analisis Kepribadian Tokoh Alara Dalam Novel Lara Rasa Karya Nureesh Vhalega Berdasarkan Teori Kebutuhan Hierarki Maslow - Debby Irola; Reni Sofia Ningsih; Eva Dwi Kurniawan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The purpose of this research is to analyze the personality of Alara. The material objects used in the novel entitled "Lara Rasa" by Nureesh Vhalega. By using a literary psychology approach. The analytical method used in this research is a descriptive qualitative method. The data obtained in this research includes all the phenomena in the novel. This phenomenon can be activities, characteristics and relationships, through critical analysis of the novel "Lara Rasa" and further analysis. This finding was obtained due to the concept of Hierarchy of Needs from Maslow. The five needs that form this hierarchy are (1) Physiological Needs, (2) Needs for Security, (3) Needs for love and Existence, (4) Needs for Appreciation, (5) The need for self-actualization. Aims to reveal personality attitudes by understanding the characters in the novel